2017
DOI: 10.1073/pnas.1713112114
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl arginine deiminase immunization induces anticitrullinated protein antibodies in mice with particular MHC types

Abstract: SignificanceThe presence and development of autoantibodies to citrullinated proteins (ACPAs) are highly associated with rheumatoid arthritis (RA). The mechanisms leading to the production of ACPAs are unknown. Here, we propose a model to explain the emergence of anticitrullinated protein autoantibodies in RA. Indeed, we could trigger the development of anticitrullinated fibrinogen autoantibodies in normal mice by immunization with peptidyl arginine deiminase (PAD), most likely through a hapten/carrier mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…In our model, anti-CCP2 was detected in the serum 4 months after PD induction, and at the same time as anti- P. gingivalis antibodies. The identified citrullinated epitope detected was similar to those recently observed in a model of T cell immunisation to PAD in mice 11. These recognised peptides encompassed resides 420–479 of the beta chain of human fibrinogen.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our model, anti-CCP2 was detected in the serum 4 months after PD induction, and at the same time as anti- P. gingivalis antibodies. The identified citrullinated epitope detected was similar to those recently observed in a model of T cell immunisation to PAD in mice 11. These recognised peptides encompassed resides 420–479 of the beta chain of human fibrinogen.…”
Section: Discussionsupporting
confidence: 80%
“…Five rats per group were sacrificed after 1 month and the others at 8 months. Rat in vivo monitoring,10 periodontitis validation, biochemistry assays and determination,11 microcomputed analysis and bone histology methods12 were described in the supplementary methods section. Non-parametric tests were performed with p values under 0.05 considered as statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that immunisation with PAD enzymes can trigger ACPA production in mice6 which might change the understanding of RA pathogenesis and increase the importance of anti-PAD antibody testing. Although several studies indicated diagnostic value of anti-PAD (especially anti-PAD4) antibodies, these antibodies are not currently used in clinical practice due to lack of commercial assays for their detection.…”
mentioning
confidence: 99%
“…Alternatively, bacterial deiminases can directly induce human immune response upon entering the human body, and anti-deiminase antibody generated against the bacterial deiminases can cross-react to the human enzymes (deiminases), leading to autoantibodies and autoimmune diseases, although neither the reports of anti-deiminase autoantibodies in human diseases are documented nor any effort is made to discover anti-deiminase antibody in autoimmune diseases. However, in mouse model, a recent study demonstrated that the immunized mice with the murine or the human PAD2 or PAD4 enzyme can generate anti-citrullinated peptide anybody, and these antibodies against citrullinated peptides only occur with the enzyme (PAD) bound to the targets (14). It appears that the immunogenic epitope is the peptide-enzyme complex.…”
Section: Discussionmentioning
confidence: 99%